Workshop on in-Depth Learning and 3D-Based Learning Media for Teachers and Students at UPTD SD Negeri 155684 Lubuk Tukko 1 - Susanti Maysura; Suryani Pulungan; Sabarita Br Tarigan; Anita Adinda (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The development of digital technology and the demands of 21st-century learning require teachers to implement meaningful and student-centered learning through an immersive learning approach. However, many elementary school teachers still face limitations in understanding the concept of immersive learning and utilizing technology-based learning media, especially three-dimensional (3D) and Artificial Intelligence (AI)-based media. Therefore, this Field Study activity aims to improve the knowledge and skills of teachers and students in implementing immersive learning through the use of 3D-based learning media and AI technology at the UPTD of SD Negeri 155684 Lubuk Tukko 1, Pandan District. The activity was implemented through a four-day workshop involving teachers and students, using an approach of socialization, demonstrations, hands-on practice, discussion, and reflection. The workshop materials covered the concept of immersive learning, the use of 3D-based learning media, gamification of learning through 3D Media applications, and the use of Artificial Intelligence in developing teaching materials and learning media. Evaluation of the activity was conducted through pre- and post-tests, participant observation, and analysis of the resulting learning products. .The results of the activity showed an increase in teachers' understanding and skills in designing and implementing technology-based immersive learning. Teachers were able to produce interactive learning media, teaching modules, and evaluation questions using 3D media, 3D media, and AI. Furthermore, this activity also increased teachers' motivation, creativity, and awareness of the importance of digital literacy in learning. This Field Study activity made a positive contribution to improving teacher competency and supporting the creation of more innovative, interactive, and relevant learning that reflects the characteristics of 21st-century learners.